A Cache Simulator for Shared Memory Systems - Schintke, Florian; Simon, Jens; Reinefeld, Alexander (Proc. Int. Conf. on Computational Science (ICCS))

RsdEditor: A Graphical User Interface for Specifying Metacomputer Components - Baraglia, Ranieri; Keller, Axel; Laforenza, Domenico; Reinefeld, Alexander (Proc. Heterogenous Computing Workshop HCW at IPDPS)
RsdEditor is a graphical user interface which produces specifications of computational resources. It is used in the RSD (Resource and Service Description) environment for specifying, registering, requesting and accessing resources and services in a metacomputer. RsdEditor was designed to be used by the administrators and users of metacomputing environments. At the administrator level, the GUI is used to describe the available computing and networking components of a metacomputer. At the user level, RsdEditor can be used to specify which characteristics of the computational resources are needed to execute a meta-application. This paper is organized as follows: it first introduces RsdEditor. It then briefly describes the RSD environment, and finally, it highlights various features and implementation issues of RsdEditor.

Werkzeugunterstützte effiziente Nutzung von Hochleistungsrechnern - Simon, Jens

Resource Management for High-Performance PC Clusters - Brune, Matthias; Keller, Axel; Reinefeld, Alexander (Proc. Int. Conf. on High-Performance Computing and Networking (HPCN))
With the recent availability of cost-effective network cards for the PCI bus, researchers have been tempted to build up large compute clusters with standard PCs. Many of them are operated with workstation cluster management software in high-throughput or single user mode. For very large clusters with more than 100 PEs, however, it becomes necessary to implement a full fledged resource management software that allows to partition the system for multi-user access. In this paper, we present our Computing Center Software (CCS), which was originally designed for managing massively parallel high-performance computers, and now adapted to modern workstation clusters. It provides - partitioning of exclusive and non-exclusive resources, - hardware-independent scheduling of interactive and batch jobs, - open, extensible interfaces to other resource management systems, - a high degree of reliability.

Specifying Resources and Services in Metacomputing Systems - Brune, Matthias; Gehring, Jörn; Keller, Axel; Reinefeld, Alexander (High-Performance Cluster Computing: Architecture and Systems)
With a steadily increasing number of services, metacomputing is now gaining importance in science and industry. Virtual organizations, autonomous agents, mobile computing services, and high-performance client–server applications are among the many examples of metacomputing services. For all of them, resource description plays a major role in organizing access, use, and administration of the computing components and software services. We present a generic Resource and Service Description (RSD) for specifying the hardware and software components of (meta-) computing environments. Its graphical interface allows metacomputer users to specify their resource requests. Its textual counterpart gives service providers the necessary flexibility to specify topology and properties of the available system and software resources. Finally, its internal object-oriented representation is used to link different resource management systems and service tools. With these three representations, our generic RSD approach is a key component for building metacomputer environments.

Managing Clusters of Geographically Distributed High-Performance Computers - Brune, Matthias; Gehring, Jörn; Keller, Axel; Reinefeld, Alexander (Concurrency, Practice, and Experience)
We present a software system for the management of geographically distributed high‐performance computers. It consists of three components: 1. The Computing Center Software (CCS) is a vendor‐independent resource management software for local HPC systems. It controls the mapping and scheduling of interactive and batch jobs on massively parallel systems; 2. The Resource and Service Description (RSD) is used by CCS for specifying and mapping hardware and software components of (meta‐)computing environments. It has a graphical user interface, a textual representation and an object‐oriented API; 3. The Service Coordination Layer (SCL) co‐ordinates the co‐operative use of resources in autonomous computing sites. It negotiates between the applications' requirements and the available system services.

Multi-User System Management on SCI Cluster - Brune, Matthias; Keller, Axel; Reinefeld, Alexander (SCI - Scalable Coherent Interface: Architecture and Software for High Performance Compute Clusters)
The growing maturity of hardware and software components has tempted researchers to build very large SCI clusters with several hundred processors that are operated as high-performance compute servers in multi-user mode. In this chapter, we present a resource management software for the user access and system administration of high-performance compute clusters named Computing Center Software (CCS). It is in day-to-day use since 1992 on various parallel systems and has recently been adapted to the management of SCI clusters. CCS provides pluggable schedulers, optimal space partitioning for multiple users, reliable user access, and powerful tools for specifying resources and services by means of a specification language and a graphical user interface. After a brief introduction in the remainder of this section, we describe the CCS system architecture and the characteristics of its resource description facilities.

Large-Scale SCI Clusters in Practice: Architecture and Performance in SCI - Simon, Jens; Reinefeld, Alexander; Heinz, Oliver (SCI: Scalable Coherent Interface. Architecture and Software for High-Performance Compute Clusters)

A Resource Description Environment for Distributed Computing Systems - Brune, Matthias; Reinefeld, Alexander; Varnholt, Jörg (Proc. Int. Symp. High-Performance Distributed Computing (HPDC))

RSD - Resource and Service Description - Brune, Matthias; Gehring, Jörn; Keller, Axel; Reinefeld, Alexander (Proc. Int. Conf. on High-Performance Computing Systems (HPCS))
RSD (Resource and Service Description) is a scheme for specifying resources and services in complex heterogeneous computing systems and metacomputing environments. At the system administrator level, RSD is used to specify the available system components, such as the number of nodes, their interconnection topology, CPU speeds, and available software packages. At the user level, a GUI provides a comfortable, high-level interface for specifying system requests. A textual editor can be used for defining repetitive and recursive structures. This gives service providers the necessary flexibility for fine-grained specification of system topologies, interconnection networks, system and software dependent properties. All these representations are mapped onto a single, coherent internal object-oriented resource representation. Dynamic aspects (like network performance, availability of compute nodes, and compute node loads) are traced at runtime and included in the resource description to allow for optimal process mapping and dynamic task load balancing at runtime at the metacomputer level. This is done in a self-organizing way, with human system operators becoming only involved when new hardware/software components are installed.

CCS Resource Management in Networked HPC Systems - Keller, Axel; Reinefeld, Alexander (Proc. Heterogenous Computing Workshop (HCW) at IPPS)
CCS is a resource management system for parallel high-performance computers. At the user level, CCS provides vendor-independent access to parallel systems. At the system administrator level, CCS offers tools for controlling (i.e, specifying, configuring and scheduling) the system components that are operated in a computing center. Hence the name "Computing Center Software". CCS provides: hardware-independent scheduling of interactive and batch jobs; partitioning of exclusive and non-exclusive resources; open, extensible interfaces to other resource management systems; a high degree of reliability (e.g. automatic restart of crashed daemons); fault tolerance in the case of network breakdowns. The authors describe CCS as one important component for the access, job distribution, and administration of networked HPC systems in a metacomputing environment.

Specifying Resources and Services in Metacomputing Environments - Brune, Matthias; Gehring, Jörn; Keller, Axel; Monien, Burkhard (Parallel Computing)
With a steadily increasing number of services, metacomputing is now gaining importance in science and industry. Virtual organizations, autonomous agents, mobile computing services, and high-performance client–server applications are among the many examples of metacomputing services. For all of them, resource description plays a major role in organizing access, use, and administration of the computing components and software services. We present a generic Resource and Service Description (RSD) for specifying the hardware and software components of (meta-) computing environments. Its graphical interface allows metacomputer users to specify their resource requests. Its textual counterpart gives service providers the necessary flexibility to specify topology and properties of the available system and software resources. Finally, its internal object-oriented representation is used to link different resource management systems and service tools. With these three representations, our generic RSD approach is a key component for building metacomputer environments.

The Latency-of-Data-Access model for Analyzing Parallel Computation - Simon, Jens; Wierum, Jens-Michael (Information Processing Letters - Special Issue on Models of Computation)

A Closer Step towards Management of Metacomputing-Resources - Brune, Matthias; Hellmann, Christian; Keller, Axel (Proc. Workshop Hypercomputing at ITG/GI-Conference Architekur von Rechensystemen)

Workload Analysis of Computation Intensive Tasks: Case Study on SPEC CPU95 Benchmarks - Simon, Jens; Weicker, Reinhold; Vieth, Marco (Proc. European Conf. on Parallel Processing (Euro-Par))

Experiences with a SCI Multiprocessor Workstation Cluster - Heinz, Oliver; Simon, Jens (Proc. Int. Conf. on Architecture of Computing Systems (ARCS))

SCI multiprocessor PC cluster in a WindowsNT environment - Simon, Jens; Heinz, Oliver (Proc. Workshops im Rahmen der 14. ITG/GI-Fachtagung Architektur von Rechensystemen)

Embedding SCI into PVM - Fischer, Markus; Simon, Jens (Proc. European Parallel Virtual Machine / Message Passing Interface Users’ Group Meeting (EuroPVM/MPI))

The MOL Project: An Open, Extensible Metacomputer - Reinefeld, Alexander; Baraglia, Ranieri; Decker, Thomas; Gehring, Jörn; Laforenza, Domenico; Ramme, Friedhelm; Römke, Thomas; Simon, Jens (Proc. Heterogenous Computing Workshop (HCW))

Sequential Performance versus Scalability: Optimizing Parallel LU-Decomposition - Simon, Jens; Wierum, Jens-Michael (Proc. Int. Conf. on High-Performance Computing and Networking (HPCN-Europe))

Performance Prediction of Benchmark Programs for Massively Parallel Architectures - Simon, Jens; Wierum, Jens-Michael (Proc. Annual Int. Conf. on High-Performance Computers (HPCS))

Accurate Performance Prediction for Massively Parallel Systems and its Applications - Simon, Jens; Wierum, Jens-Michael (Proc. European Conf. on Parallel Processing (Euro-Par))

On Accurate Performance Prediction for Massively Parallel Systems and its Applications - Simon, Jens; Wierum, Jens-Michael

Implementation of a Parallel and Distributed Mapping Kernel for PARIX - Röttger, Markus; Schroeder, Ulf-Peter; Simon, Jens (Proc. Int. Conf. on High-Performance Computing and Networking)

An Efficient Mapping Library for Parix - Römke, Thomas; Röttger, Markus; Schroeder, Ulf-Peter; Simon, Jens (Proc. ZEUS Workshop on Par. Programming and Computation)

On Efficient Embeddings of Grids into Grids in PARIX - Römke, Thomas; Röttger, Markus; Schroeder, Ulf-Peter; Simon, Jens (Proc. European Conf. on Parallel Processing (Euro-Par))

SparcStation SCI-Interface - Gehring, Jörn; Simon, Jens

Parallel CG Poisson Solver for PowerPC 601 - Blazy, Stephan; Dralle, Uwe; Simon, Jens (PowerXplorer User Report - Applications and Projects on the Parsytec PowerXplorer Parallel Computer)

Leistung eines Parallelrechners auf Basis des PowerPC-Prozessors - Simon, Jens (Parallele Datenverarbeitung aktuell: TAT '94)

Benutzung virtueller Topologien unter PARIX - Simon, Jens

Virtual Topology Library for PARIX - Röttger, Markus; Simon, Jens; Schroeder, Ulf-Peter

Problem Independent Distributed Simulated Annealing and its Applications - Diekmann, Ralf; Lüling, Reinhard; Simon, Jens

Problem Independent Distributed Simulated Annealing and its Applications - Diekmann, Ralf; Simon, Jens (Applied Simulated Annealing)

Leistungssteigerung paralleler Systeme durch virtuelle Topologien - Diekmann, Ralf; Simon, Jens (Abstraktband des 4. bundesweiten Transputer-Anwender-Treffens (TAT 92))

A General Purpose Distributed Implementation of Simulated Annealing - Diekmann, Ralf; Lüling, Reinhard; Simon, Jens (Proc. 13th IMACS World Congress on Computation and Applied Mathematics)

A General Purpose Distributed Implementation of Simulated Annealing - Diekmann, Ralf; Lüling, Reinhard; Simon, Jens (Proc. IEEE Symp. on Parallel and Distributed Processing (SPDP))

Implementierung von Simulated Annealing auf Transputer-Systemen - Diekmann, Ralf; Lüling, Reinhard; Monien, Burkhard; Simon, Jens (Parallele Datenverarbeitung mit dem Transputer)